The effect of Zinc Oxide nanoparticles on Pseudomonas aeruginosa biofilm formation and virulence genes expression - Wedad Mahmoud Abdelraheem; Ebtisam S Mohamed (Journal of Infection in Developing Countries)
Introduction: Due to increased resistance to antimicrobial agents, infectious diseases remain a public health problem worldwide. The current study was designed to examine the effect of Zinc Oxide nanoparticles (ZnO–np) against the biofilm formation ability of P. aeruginosa clinical isolates and to study its effect on the expression level of the genes involved in biofilm formation and virulence factors production.